The Use of Laparoscopic Technologies in the Treatment of Patients with Complicated Forms of Colon Cancer - Kubrak, Mykhailo; Zavgorodnii, Serhiy; Danilyk, Mykhailo (Futurity Medicine, 2025)
Aim of the study. To analyze the outcomes of using laparoscopic methods in the treatment of patients with complicated forms of malignant colon diseases. Materials and Methods. A prospective cohort study included 109 (100 %) patients with complicated forms of colon cancer. 74 (67.89 %) patients had tumor-induced acute intestinal obstruction (AIO); 21 (19.27 %) had tumor perforation; 6 (5.50 %) had acute gastrointestinal bleeding (GIB); 3 (2.75 %) had both AIO and perforation; and 5 (4.59 %) had both AIO and bleeding. Results. Emergency surgeries were performed in 18 (16.51 %) patients, urgent surgeries in 17 (15.60 %), and delayed surgeries in 74 (67.89 %). Laparoscopic techniques were used in 31 (28.44 %) cases. In 71 (65.13 %) patients, laparotomy was performed. Postoperative complications occurred in 6 (19.35 %) laparoscopic cases, compared to 32 (41.03 %) laparotomy cases (p = 0.0286). Wound complications (seromas, hematomas, infiltrates, infections, dehiscence) were more frequent in the laparotomy group — 17 (21.79 %) vs. 1 (3.23 %) in the laparoscopic group (p = 0.0083). Mortality was 5 (16.13 %) in the laparoscopic group and 18 (23.08 %) in the laparotomy group (p = 0.3781). Average hospital stay: 10.00 (8.00; 13.00) days for laparoscopy vs. 19.00 (13.00; 27.00) days for laparotomy (p = 0.0011). Conclusions. Laparoscopic surgery methods can be applied in treating all types of complicated colon cancer. This type of surgery reduces postoperative complications and hospital stay in research group.